A Universal Quantitative Descriptor of the Dispersion Interaction Potential. Issue 29 (24th June 2019) - Pollice, Robert; Chen, Peter
Abstract: London dispersion, universally attractive forces originating from fluctuating dipoles, is omnipresent in molecules. While its understanding has recently made tremendous progress, its general appreciation is still lagging behind electrostatics. This can be explained by the simple tools available to study electrostatic interactions, such as electrostatic potential (ESP) maps and partial charges, and a lack thereof for dispersion. We herein report a universal quantitative descriptor of dispersion interaction potentials, which allows assessing dispersion visually by London dispersion potential (LDP) maps, and quantitatively using the average LDP on the van der Waals surface. We demonstrate the utility of these new tools by constructing a quantitative dispersion energy scale of the elements and common substituents, studying non‐covalent interactions (NCIs), and developing modern linear free energy relationships in catalysis. Abstract : A map of London : A new descriptor of the quantitative dispersion interaction potential is introduced and applied to the study of non‐covalent interactions in spectroscopy, nanomaterials, and catalysis. It allows the generation of London dispersion potential maps indicating the site of strongest dispersion and the estimation of average dispersion interaction strengths of any atom or molecule.